IMPELEMENTASI ANGGOTA. TNI-POLRI LMENJADI PELAKSANAI TUGAS KEPALA DAERAH - Nabilah, Idzahti Fitri; Suhartono, Slamet (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Filling the Vacant Regional Head is the most important. thing for the, continuity. of, governance in the region. This is because not all Regional Heads who occupy positions have the same time range for ousting. This is due to the existence, of new laws, and- regulations to equalize terms of office in all regions in Indonesia. The implications of job requirements that can fill the vacancy in this position have caused debate among the public and academics. In this research, a normative juridical approach is used. Normative legal review is a process of exploration, discovery and discovery of legal principles, legal rules and legal cases that will be used to respond to legal issues. Them results of the research show, that activei membersl of. the POLRI and. TNI soldiers are not allowed to occupy positions in the government that have nothing to do with their identity. Even their political rights are also limited, they can occupy civil political positions if they have resigned or have retired. This is reinforced by Law no. 2/ 2002 and Law no. 34/2004 has clearly limited the political rights of POLRI members and TNI soldiers. Ini this, case it can be. seen lin Article 28 of Law no. 2/ 2002 and Article 39 of Law no. 34/2004. If this position is seen from the ASN elements, it can be concluded that only acting ASN employees can fill this position